(untitled) (Journal of Hama University, 2021)
Coccidiosis in chickens is one of the most common and occurring disease in chickens. It is associated with significant economic losses due to the high mortality rates and the low feed conversion ratio as a result of Pathological Changes in the intestine. Eimeria maxima is one of Eimeria species that causes coccidiosis in chickens between the age of (2-6) weeks, causing major lesions in the middle part of the small intestine 2300 Broiler Chickens were examined visually and 180 samples of meat chicken intestines collected from 56 Broiler flocks 2 to 6 week old were examined to determine the severity of pathological changes caused by Eimeria maxima infection. it was found that 9 flocks were infected with E. maxima with an infection rate of 16% The severity of the pathological changes have been studied, which included distention of the middle part of the intestine, reaching almost twice its normal size, lumen was filled with blood cloths, tissue debris and fluids. The histopathology of midgut of affected birds revealed The presence of large numbers of schizonts in the submucosal layer and the lamina propria, in addition to degeneration of the intestinal villi and epithelium .The Microscopic lesions extended severely to muscular layers and reached the boarder of serosal layer.